S2_1 Getting comfortable on Neptune - Berry, Tom; Erojo, Anthony; Taylor, Ben (Physics Special Topics, 2017)
The effects of long term exposure to high gravity on human health are not well understood but will likely prove to be problematic. Therefore, if humans wish to colonise planets with signicantly higher gravity than Earth then it may be necessary to engineer solutions to articially reduce the effects of gravity. This paper assesses the admittedly elaborate idea to use the centrifugal and Coriolis effects to articially reduce the effects of gravity through increasing a planet's rotation. We decided to use Neptune as an example but the concepts and maths used in this paper should be applicable to any planet. We worked out that we would need to speed up Neptune's rotation by 6.12*10-5rads-1 to simulate a downwards acceleration of 9ms-2 at the equator and that this would require an impulse of 6.2*1028Ns.